Contribuições das capacidades dinâmicas para a responsividade do processo de inovação responsável: um estudo de caso na indústria de transformação do Brasil - Vila Nova, Silvânia da Rocha Medeiros (Universidade do Vale do Rio dos Sinos, 2023)
Responsible innovation has been considered a promising area of study to face the challenges of the transition to a sustainable economic development model. Researchers have recommended that companies improve the responsiveness of the innovation process to improve both the process and the results of innovations. However, many companies have failed to improve responsiveness in their innovation processes. Studies indicate that this challenge can be overcome with the support of new approaches, including the development of dynamic capabilities. However, even though it is important, the academic literature still does not explore, in the necessary detail, the effects that dynamic capabilities can have on responsible innovation. Furthermore, the contributions that dynamic capabilities and their microfoundations can offer to facilitate the development of the responsible innovation process still require further investigation. This study aims to analyze how dynamic capabilities can contribute to enhance the responsiveness dimension of the responsible innovation process. Through qualitative research, with a case study approach, we sought to deepen the understanding of the contributions of dynamic capabilities to improve the development of the responsible innovation process. The research results show that distinct microfoundations of the dynamic capabilities sensing, seizing, and reconfiguring can strengthen attributes of the responsible innovation process responsiveness, contributing to enhance its impact on innovations. These findings expand knowledge about the impact of dynamic capabilities on the responsible innovation process, deepen knowledge about how dynamic capabilities and their microfoundations can influence the development of the responsiveness dimension of the responsible innovation process. The results contribute to overcoming business challenges aimed at strengthening their innovative activities, refining the understanding of processes, skills, routines and organizational procedures necessary for identifying and taking advantage of new opportunities, as well as so that the realignment of internal processes has a greater chance of success.
Keywords: Responsividade; Inovação responsável; Capacidades dinâmicas; Microfundamentos; Sul global; Responsiveness; Responsible innovation; Dynamic capabilities; Microfoundations; Global south; ACCNPQ::Ciências Sociais Aplicadas::Administração